2020
DOI: 10.1001/jamadermatol.2020.3275
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical and Demographic Factors With the Severity of Palmoplantar Pustulosis

Abstract: ; for the ERASPEN consortium and the APRICOT and PLUM study team IMPORTANCE Although palmoplantar pustulosis (PPP) can significantly impact quality of life, the factors underlying disease severity have not been studied. OBJECTIVE To examine the factors associated with PPP severity. DESIGN, SETTING, AND PARTICIPANTS An observational, cross-sectional study of 2 cohorts was conducted. A UK data set including 203 patients was obtained through the Anakinra in Pustular Psoriasis, Response in a Controlled Trial (2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 29 publications
(43 reference statements)
9
29
2
Order By: Relevance
“…In the current study, the prevalence of a positive family history was 8.3% for PPP and slightly higher (9.5%) for PsV. A similar pattern of family history prevalence being lower for PPP and higher for PsV was reported in previous studies, with ranges of 0%–11% and 1.5%–32%, respectively 5,8–10,15,20 . These results support a shared genetic background between PPP and PsV.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, the prevalence of a positive family history was 8.3% for PPP and slightly higher (9.5%) for PsV. A similar pattern of family history prevalence being lower for PPP and higher for PsV was reported in previous studies, with ranges of 0%–11% and 1.5%–32%, respectively 5,8–10,15,20 . These results support a shared genetic background between PPP and PsV.…”
Section: Discussionsupporting
confidence: 90%
“…This can be explained by the fact that both BMI and prevalence of obesity is considerably higher in Turkish women (30%) than in men (17%) in the general Turkish population 16 . We also aimed to identify whether there is an association between obesity and disease severity, as few studies have examined this association 3,9,17 . Consistent with two previous studies, 3,9 we found no association between higher PPPASI and either mean BMI or frequency of overweight/obesity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In 2017, Trattner et al . in a cross-sectional study demonstrated a direct correlation between severity, measured by PalmoPlantar Pustulosis Severity Index (PPPASI), and QoL impairment, measured by Dermatology Life Quality Index (DLQI), data recently confirmed in a larger study including UK and Northern European patients 10 , 16 . PPP severity seems to be higher in female versus male patients and in current or past smokers 10 .…”
Section: Clinical Presentation and Severity Assessmentmentioning
confidence: 71%
“…The prevalence of PV among PPP patients ranges from 14 to 61% 10 13 . Nail involvement (nail psoriasis) in PPP seems to be frequent, ranging from 30 to 76% 2 .…”
Section: Epidemiologymentioning
confidence: 99%